HUBUNGAN ADVERSITY QUOTIENT DENGAN PERSEPSI TENTANG HIDUP HEMAT PADA SISWA JURUSAN IPS SMA NEGERI 1 KANDANGAN MUHAMAD RIZA - Muhammad Riza (Universitas Lambung Mangkurat, 2012)
Adversity Quotient is a reflection of a person when faced with the challenge / problem, which in this case are grouped into three groups: quitters, campers, and climbers.This study aims to determine the relationship adversity quotient by perceptions of life saving social science students Prgrams of SMAN 1 Kandangan HSS Regency.The study was conducted at SMAN 1 Kandangan HSS Regency, South Kalimantan. The method used is a correlational method. Variables that were tested are variable AQ and perceptions about life saver. Subjects were students of the Sosial Science Program Academic year 2011/2012 amounted to 218 people. Data collection techniques are the questionnaire technique. Data obtained in the field and then analyzed quantitatively.The results of the study show that the AQ Student Programs IPS SMAN 1 Kandangan proportion 49.3% (campers) and 50.7% (climbers).Proportion of 4 (four) AQ indicator that states X1 control was 32% (quitters) 56% (campers), and 12% (climbers). Origin and ownership X2 is 29.3% (quitters), 4% (campers) and 66.7% (climbers). Reach X3 is 26.7% (quitters), 58.7% (campers), and 14.7% (climbers). Endurance X4 is 37.3% (quitters), 44% (campers) and 18.7% (climbers). The results of simple correlation analysis of the relationship between the Y X1 coefficient of 0.239 or p <0.05 is significant, the coefficient of X2 with Y obtained at 0.279 or p <0.05 is significant, the coefficient of X3 to Y obtained at 0, 230 or p <0.05 is significant, between X4 with coefficient Y of 0.327 or p <0.05 is significant, and for the variable total score of the adversity quotient (X) with perceptions about life saving (Y) obtained by the correlation coefficient of 0.342 or p <0.05 is significant. The results of partial correlation analysis the relationship between the level I controlled X1 X to Y is obtained coefficient 0.259 or p <0.05 is significant, the relationship X to Y is controlled by the coefficient obtained X3 0.264 or p <0.05 was significant. The results of partial correlation analysis the relationship level II controlled variable X with Y CR coefficient 0.264 or p <0.05 was significant. The results of partial correlation analysis level III controlled the relationship X with Y CO2R coefficient 0.216 or p <0.05 was significant.Follow-up related to this study is that students who have a high AQ will have an impact on the hide perception on life-saving, so the development of AQ at school needs to be done so that students are able to apply the life-saving manner better.Keywords: Perceptions about saving lives, adversity quotient.